The meaning of nihilism in the philosophy of Friedrich Nietzsche - Dodds, Martine M. E.(Martine Marguerite Elizabeth) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1984.